2006
DOI: 10.2225/vol9-issue2-fulltext-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bacillus thuringiensis insecticidal protein gene in transgenic oil palm

Abstract: Oil palm, like all other crops, is susceptible to attack from several insect pests causing significant reduction in productivity. In the past, cry genes from Bacillus thuringiensis have been reported to be effective in conferring resistance towards insect pests in crops such as corn and rice. One of the advantages of these toxin proteins is their specificity towards certain harmful insects. A rapid and efficient method was developed for the transformation and evaluation of CryIA(b) expression in oil palm. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Furthermore, knowledge of insecticidal proteins elucidates genes that can be harnessed in producing insect‐resistant genetically‐modified crops. A well‐established model is the Bt toxin‐producing crops applied across a wide range of crop types (Lee, Yeun, & Abdullah, ; ISAAA, n.d.). However, the effectiveness of proteomics in providing insight of EPMs’ biology has a caveat.…”
Section: Promises and Caveat Of Proteomics For Bioinsecticide Researchmentioning
confidence: 99%
“…Furthermore, knowledge of insecticidal proteins elucidates genes that can be harnessed in producing insect‐resistant genetically‐modified crops. A well‐established model is the Bt toxin‐producing crops applied across a wide range of crop types (Lee, Yeun, & Abdullah, ; ISAAA, n.d.). However, the effectiveness of proteomics in providing insight of EPMs’ biology has a caveat.…”
Section: Promises and Caveat Of Proteomics For Bioinsecticide Researchmentioning
confidence: 99%
“…Regarding to biotic factors, [71] introduced a synthetic cryIA(b) gene into oil palm while biobalistic. When cryIA(b) gene was expressed, it produced proteins which upon crystallization are highly toxic to Lepidoptera among which, Metisa plana is a major insect pest for oil palm.…”
Section: Advances In Seed Biology 304mentioning
confidence: 99%
“…In mature open flowers, staining was observed in the green bract surrounding the flower, in the green ovary wall and in the stigma, and in pollen, but not in ovules. Lee et al (2006) reported the integration and expression of the cry1A(b) insecticidal gene under rbcs promoter in transformed oil palm. A biolistic method was used to transform immature embryos (IEs) of oil palm.…”
Section: Rubisco Small Subunit Promoter As a Green Tissue-specific Prmentioning
confidence: 99%